Nutritional programming of brown adipose tissue - Alagal, Reham (2018)
Maintenance of functional brown adipose tissue (BAT) beyond the newborn period, through its role in expending energy in thermogenesis, provides a potential target to prevent childhood obesity. As the body’s fat distribution can be programmed by nutrition in early life, this study investigated whether modifying the maternal diet in the immediate newborn period increases the thermogenic potential of major brown fat depots. In humans and sheep, UCP1 decreases after birth, thus, BAT gradually transitions to be white adipose tissue (WAT). Three major adipose tissue depots in sheep (sternal, perirenal and epicardial) were studied which are all populated with brown adipocytes in early postnatal life, and then undergo a transition to WAT by the end of first month of life. Heat production in BAT is mediated by uncoupling protein (UCP)1 and fatty acids have the potential to increase the amount of UCP1. The aim of this thesis was, therefore, to determine whether maternal fatty acid supplementation with a readily available short-chain fatty acid (i.e. canola or sunflower oil) modifies milk fatty acid profile and thus the development of adipose tissue in the offspring.